Determinants of economic and social empowerment of rural women in the Al-Haffa region (Journal of Hama University, 2025)
Abstract:The research aimed to study the determinants of the economic and social empowerment of rural women in the Al-Haffa region, and to study the effect of both educational level and income on the economic and social empowerment of women, The descriptive analytical approach was relied upon to characterize and analyze the sample members’ answers to the questionnaire questions, The quantitative approach was also used using appropriate tests such as the multiple analysis of variance test. The results showed that the most important determinants of rural women’s economic empowerment are their low ability to compete in the labor market, their low percentage of land and property ownership, and their weak participation in economic studies for projects to be established. It also turned out that the most important determinants of rural women’s social empowerment are their weak participation in membership in local organizations. The inability of women's unions to sponsor women's rights, and the weakness of informal social participation in decision-making at the village level. The results of testing the research hypotheses showed that there are statistically significant differences in the level of economic and social empowerment of women, depending on educational and income. Keywords: economic empowerment, social empowerment, Al-Haffa, Rural women.
Keywords: Keywords: economic empowerment, social empowerment, Al-Haffa, Rural women.